Case report: Nutritionally supported perioperative chemo-immunotherapy for advanced gastric cancer with incomplete pyloric obstruction - Jian, Mi; Yang, Zhensong; Hu, Xue; Wang, Xixun; Zhang, Zhenbin; Zhang, Yifei; Song, Xinna (Frontiers in Oncology, 2024)
This case describes the benefits of perioperative chemo-immunotherapy for advanced gastric cancer and incomplete pyloric obstruction, supplemented with nutritional support. Early parenteral nutrition to stabilize nutritional status and mitigate nutrition impact symptoms, and in addition, throughout the chemo-immunotherapy perioperative period also maintained oral nutrition support and a tailored dietary plan. Above nutritional support maintained the patient's physical condition during immunotherapy. Eventually, this combination therapy plan leads to a partial response. On the other hand, a combination of therapies that focus more on immune checkpoint inhibitor may be able to mitigate the side effects of chemotherapy. Such findings may yield novel prospects for patients with advanced gastric cancer and incomplete pyloric obstruction, enabling them to achieve better outcomes.